An efficient gateway routing scheme for disaster recovery scenario - Nor Aida, Mahiddin; Sarkar, N (2019)
Natural disaster can strike at any time and can ruin large regions damaging houses, buildings, as well as physical communication infrastructure. Therefore, a network backup is essential in the disaster recovery areas as victims can contact their loved one in order to update the current situation as soon as possible. A mobile ad hoc network (MANET) is a collection of mobile devices that dynamically communicate with each other without any physical infrastructure. This feature offers a solution for communication problems in disaster recovery and keeping the communication going in disaster areas. In this paper we propose an efficient routing selection scheme (GWRS) to overcome traffic congestion problems due to huge calls in disaster areas network. This new scheme provides a flexible and feasible approach in determining the best route. The routing scheme will simplify the selection of routes and prevent nodes from broadcasting packets to the entire network. In addition, this scheme eradicates any redundant nodes in each level of the routing table. Ad-Hoc On-Demand Distance Vector (AODV) and Destination Sequenced Distance Vector (DSDV) routing schemes was chose because the schemes show the best performance for reactive and proactive categories respectively in emergency scenarios. These schemes simulated in the same realistic environment of disaster recovery area. Then, the performance of the proposed scheme is compared to these two schemes.